Fenomena Thrift Shop Dikalangan Remaja: - Nella Linggar Adji; Dyva Claretta (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This study examines how the phenomenon of shopping for imported used clothes is still suitable for use, which is commonly known as thrift. Many teenagers, especially in Surabaya, are interested in thrifting activities at their favorite thrift shop. This habit gives rise to a new culture commonly known as popular culture, a trend that is currently emerging, favored and created by the community. The purpose of this study was to find out how the understanding, experience, and motivation of the community, especially among Surabaya teenagers regarding the